Effect of LSKL peptide on thrombospondin 1‐mediated transforming growth factor β signal activation and liver regeneration after hepatectomy in an experimental model. Issue 7 (13th April 2015) - Kuroki, H.; Hayashi, H.; Nakagawa, S.; Sakamoto, K.; Higashi, T.; Nitta, H.; Hashimoto, D.; Chikamoto, A.; Beppu, T.; Baba, H.
<x xml:space="preserve">Abstract</x> Background A strategy for accelerating liver regeneration after hepatectomy would offer great benefits in preventing postoperative liver failure and improving surgical outcomes. Transforming growth factor (TGF) β is a potent inhibitor of hepatocyte proliferation. Recently, thrombospondin (TSP) 1 has been identified as a negative regulator of liver regeneration by activation of local TGF‐β signals. This study aimed to clarify whether the LSKL (leucine–serine–lysine–leucine) peptide, which inhibits TSP‐1‐mediated TGF‐β activation, promotes liver regeneration after hepatectomy in mice. Methods Mice were operated on with a 70 per cent hepatectomy or sham procedure. Operated mice received either LSKL peptide or normal saline intraperitoneally at abdominal closure and 6 h after hepatectomy. Perioperative plasma TSP‐1 levels were measured by enzyme‐linked immunosorbent assay in patients undergoing hepatectomy. Results Administration of LSKL peptide attenuated Smad2 phosphorylation at 6 h. S‐phase entry of hepatocytes was accelerated at 24 and 48 h by LSKL peptide, which resulted in faster recovery of the residual liver and bodyweight. Haematoxylin and eosin tissue staining and blood biochemical examinations revealed no significant adverse effects following the two LSKL peptide administrations. In the clinical setting, plasma TSP‐1 levels were lowest on the first day after hepatectomy. However, plasma TSP‐1 levels at this stage were significantly higher in patients with subsequent liver dysfunction compared with levels in those without liver dysfunction following hepatectomy. Conclusion Only two doses of LSKL peptide during the early period after hepatectomy can promote liver regeneration. The transient inhibition of TSP‐1/TGF‐β signal activation using LSKL peptide soon after hepatectomy may be a promising strategy to promote subsequent liver regeneration.<boxed-text content-type="box" id="bjs9765-blkfxd-0001" position="anchor" orientation="portrait"> Surgical relevance Although the mechanisms of liver regeneration after hepatectomy have been explored intensively in vivo, no therapeutic tools are thus far available to accelerate liver regeneration after hepatectomy in the clinical setting. Recently, the matricellular protein thrombospondin (TSP) 1, a major activator of latent transforming growth factor (TGF) β1, has been identified as a negative regulator of liver regeneration after hepatectomy. In this study, the inhibition of TSP‐1‐mediated TGF‐β signal activation by LSKL (leucine–serine–lysine–leucine) peptide in the early period after hepatectomy accelerated liver regeneration without any adverse effects. In addition, continuous high plasma TSP‐1 levels after hepatectomy were associated with liver damage in humans. The transient inhibition of TSP‐1/TGF‐β signal activation using LSKL peptide in the early period after hepatectomy could be a novel therapeutic strategy to accelerate liver regeneration after hepatectomy. </boxed-text>